Factorial studies with fractional replication of mineral fertilization of the peanut - Britto, Dirce P.P. de Souza; Arruda, Norma Bergallo de; Nery, Clovis; Eira, Paulo Augusto da (Pesquisa Agropecuaria Brasileira, 2014)
An investigation of the response of peanut (Arachis hypogaea L.) to nitrogen, phosphorus, potassium, calcium, magnesium fertilization and interactions of these elements is reported. The results obtained were also used for a comparative study of the complete 25 factorial scheme and fractional schemes, using the same data. The work brings together the results of six years of experimentation, in which the trials were repeated in the same local for four years. In the last two years, residual effects of fertilizers were studied. The experiments were carried out at the Experimental Station of São Simão, São Paulo, which presently belongs to the network of the Meridional Region Institute of Agricultural Research (Instituto de Pesquisa Agropecuária Meridional). From the combined analysis of data of the years in which the fertilizers were applied, it was concluded that the greatest necessities of the peanut in the studied soil (a "terra roxa de campo" with low fertility) were phosphorus, calcium, and magnesium. There was an indication that the phosphorus and the calcium had residual effects two years after the last fertilizers were applied. The analysis showed a positive effect of nitrogen when the influence of the principal elements and third order interactions was investigated; but in the complete analysis, no significance for this element was demonstrated. The increase in the yield of peanuts from the significant macro nutrients was not great, but it should be noted that the levels of the elements used were quite low. The study of the use of fractional schemes sought to determine if they gave the same results as the complete scheme. The fractional scheme - NPKCaMg, presented a good agreement with the complete scheme for some of the variables studied (calcium and magnesium) and did not show significance for phosphorus and nitrogen. For this reason, this scheme can not be indicated to substitute the complete scheme.